Butadiene Sulfone-catalyzed Monobromination of Arenes with NBS as the Bromination Source: A Simple, Mild, Efficient, and Chemoselective Protocol - Sharma, Amit; Rudrawar, Santosh; Jadhav, Hemant R. (Letters in Organic Chemistry, 2024)
In literature, dimethyl sulfoxide (DMSO) catalyzed bromination of arenes and heteroarenes is reported. In this study, simple, mild, and chemoselective N-bromosuccinimide (NBS) mediated monobromination of arenes and heteroarenes using butadiene sulfone as a catalyst is reported.Butadiene sulfone is a good substitute for DMSO as it is volatile, easy to recover and recycle, and environment- friendly. The method has been demonstrated to give high-yield brominated products for an extensive range of activated and deactivated arenes.
Keywords: chemoselective synthesis